Pengaruh Struktur Modal, Likuiditas, dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan Sektor Pertambangan Batu Barayang Terdaftar Pada Bursa Efek Indonesia (BEI) Periode 2018-2021 - Susena, Dicken Okta Sandra; Ady, Sri Utamy (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of capital structure (DER), liquidity (CR), and company size (SIZE) on the profitability of coal mining companies on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. Using 24 coal mining sector companies as samples, this study used the Common Effect Model (CEM), Random Effect Model (REM), Fixed Effect Model (FEM) test to find the best model and it was found that the FEM model was the best. The data analysis technique used the Ordinary Least Square (OLS) method, using the Eviews 10 program. The results showed that Capital Structure (DER), Liquidity (CR) had an insignificant negative effect, and Company Size (SIZE) had a significant negative effect on Profitability (ROA). Simultaneously, Capital Structure (DER), Liquidity (CR), and Firm Size (SIZE) have a significant effect on Profitability (ROA).The results of the coefficient of determination test show that Capital Structure (DER), Liquidity (CR), and Firm Size (SIZE) has an effect of 18.8168% on profitability that the correlation between capital structure (DER), liquidity (CR), and company size (SIZE) on profitability (ROA) is very low.